Analisis Peran Pemerintah dalam Program Pemberdayaan Ekonomi Berbasis Komunitas - Muhammad Fawwaz Zufar Mokke; Made Suwandi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Population growth that is not accompanied by support for human resource development can lead to problems such as managing economic and social dynamics in sectors that require development and training to fulfill the role of government. The purpose of this research is to analyze a deep understanding of the role of government in overcoming socio-economic conflicts through economic communities and which factors influence the process of economic empowerment. This study uses a descriptive analytical method with a qualitative approach. Research results show that economic-based community empowerment programs effectively promote sustainability and improve human well-being. The effectiveness of the program is influenced by active community participation, government involvement, development of knowledge and capacity, and use of local resources. Therefore, community-based economic empowerment programs should be designed with these factors in mind to provide optimal benefits to the community.